Wage subsidies in developing countries as a tool to build human capital: Design and implementation issues - Rita Almeida; Larry Orr; David Robalino (IZA Journal of Labor Policy, 2014)
This paper reviews international experiences with the implementation of wage subsidies and develops a policy framework to guide their design in developing countries. The evidence suggests that, if the goal is only to create jobs, wage subsidies are unlikely to be an effective instrument. Wage subsidies, however, could have a role in helping first-time job seekers or those who have gone through long-periods of unemployment or inactivity, to gain some work experience and in the process build skills and improve their employability. If these "learning" effects are large enough, the social benefits of wage subsidies could outweigh their cost. When wage subsidies are designed with these objectives in mind, there are important implications in terms of eligibility and targeting, how the subsidy is set, its duration, and the types of conditionalities on employers and beneficiaries. Given uncertainty regarding their impact, in all cases, programs should be piloted and evaluated prior to full scale implementation.
Keywords: J2; J3; J6; 330; Wage subsidies; Learning by doing; Skills; Unemployment